ECTOPIC CUSHING’S SYNDROME: THE LONG HUNT FOR THE ELUSIVE CULPRIT - Lee, Teck Wui; Tan, Hai Kiang; Nazlee, Asma’ Mohd; Chan, Pei Lin; Kuan, Yueh Chien; Tan, Florence Hui Sieng (Journal of the ASEAN Federation of Endocrine Societies, 2025)
INTRODUCTION/BACKGROUND Ectopic Cushing’s Syndrome (ECS), caused by non-pituitary ACTH-secreting tumours, is a rare but life-threatening form of hypercortisolism. Diagnosis and management can be challenging due to the small, indolent tumours of variable locations. We present two cases highlighting the complexity of diagnosing and managing ECS. CASE A 70-year-old male presented with hypertensive urgency, hypokalemia (K⁺ 1.9 mmol/L), and new-onset diabetes mellitus (HbA1c 7.1%). He required four antihypertensives, dual oral antidiabetic therapy and potassium supplementation. Investigations revealed markedly elevated cortisol (3026 nmol/L), non-suppressible with dexamethasone (1750 nmol/L), and high ACTH (500 pg/mL) consistent with ACTH-dependent Cushing’s Syndrome (CS). Initial Thorax-Abdomen-Pelvis CT, pituitary MRI and Gallium-68 PET scans were unremarkable. Treatment with ketoconazole and spironolactone led to clinical improvement, allowing discontinuation of antihypertensives, antidiabetics and potassium supplements. Serial CT TAP later detected an enlarging 1.2 cm right middle lobe lung nodule. Surgical resection confirmed an ACTH-positive carcinoid tumour. The patient remained in remission for 6.5 years post-operatively. A 59-year-old female with poorly controlled hypertension and diabetes was found to be cushingoid during hospitalisation for a finger abscess. Cortisol was 1164 nmol/L, ACTH 19.5 pmol/L, with non-suppression to dexamethasone. Conventional imaging (CT TAP, pituitary MRI, PET scan) showed no significant abnormality. However, IPSS confirmed an ectopic ACTH source. She exhibited cyclical CS, which was marked by fluctuations in blood pressure, glucose, potassium levels, weight and oedema. Management required a block-and-replace regimen using ketoconazole and hydrocortisone. A Ga-68-DOTATATE PET scan two years later revealed a DOTATATE-avid right lung nodule, but the biopsy was inconclusive. The patient declined further procedures. CONCLUSION These cases highlight the diagnostic complexity of ECS, which has required multimodal and serial imaging over the years due to elusive lesions. Biochemical control can be challenging due to cyclical CS demanding balance to avoid complications. Persistent localisation efforts remain essential as surgical resection is potentially curative.